(untitled) (International Journal of Engineering and Computer Science, 2014)
Image registration is a current area of research in many areas like medicine, remote sensing and many more. This paper illustrates the various techniques of image registration providing advantages and disadvantages of these techniques and an overall understanding of image registration. Image registration is a process of overlaying two or more images of the same scene taken at different times, from different viewpoints, or by different sensors. Image registration is a crucial step in all image analysis tasks. This paper would help the researchers to have a full understanding of image registration process.